Increased Neutrophil Aging Contributes to T Cell Immune Suppression by PD-L1 and Arginase-1 in HIV-1 Treatment Naïve Patients - Liu, Kai; Huang, Hui-Huang; Yang, Tao; Jiao, Yan-Mei; Zhang, Chao; Song, Jin-Wen; Zhang, Ji-Yuan; Zhou, Chun-Bao; Yuan, Jin-Hong; Cao, Wen-Jing; Mu, Xiu-Ying; Zhou, Ming-Ju; et al. (Frontiers in Immunology, 2021)
Neutrophils are characterized by heterogeneity, with capacity to fight against pathogens, and involved in tissue injury repair and immune system regulation. Generally, neutrophils have a very short life span in the peripheral blood, and undergone the process of aging after release from bone marrow. Under some pathological conditions, the over-aggregation of aged neutrophils occurred and is associated with phenotypic and functional change, which may lead to T cell immuno-dysfunction. During HIV-1 infection, the dynamics of neutrophil aging and its role in mediating T cell exhaustion are not well understood. In the study, we enrolled 23 treatment naïve (TN) patients, 23 ART (antiretroviral therapy)-treated individuals and 21 healthy controls (HC). In these cohorts we measured the status of aged neutrophils and the correlation with T cell activation levels. In TN patients, peripheral neutrophils have a significantly higher aging phenotype and were over-activated. The aging of neutrophils is positively correlated with HIV-1 RNA levels, and have impaired reactive oxygen species (ROS) production after LPS stimulation. Simultaneously, aged neutrophils were characterized by increased PD-L1 and arginase-1 expression in a time-depended manner. The aged neutrophils demonstrated a higher capacity to inhibit CD8+ T cell secreting IFN-γ and TNF-α compared to non-aged neutrophils. The inhibition effect was reversed by anti-PD-L1 and anti-arginase-1 blocking in vitro. Finally, LPS was identified as an important activator to initiate the process of neutrophil aging. These results provide evidence that dampening neutrophil aging may provide a novel approach to recover T cell dysfunction in HIV-1 patients.